2017
DOI: 10.1038/s41598-017-08060-4
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and modelling the response of Klebsiella pneumoniae KPC prey to Bdellovibrio bacteriovorus predation, in human serum and defined buffer

Abstract: In worldwide conditions of increasingly antibiotic-resistant hospital infections, it is important to research alternative therapies. Bdellovibrio bacteriovorus bacteria naturally prey on Gram-negative pathogens, including antibiotic-resistant strains and so B. bacteriovorus have been proposed as “living antibiotics” to combat antimicrobially-resistant pathogens. Predator-prey interactions are complex and can be altered by environmental components. To be effective B. bacteriovorus predation needs to work in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 44 publications
1
38
0
7
Order By: Relevance
“…The predatory phenotypes observed during NC01 co-culture with E. coli ML35 may be the result of a mechanism specific to the prey, the predator, or a combination of the two. Other researchers have observed prey population recovery [66,67], and Shemesh and Jurkevitch demonstrated that recovery of Erwinia carotovora in co-cultures with Bdellovibrio isolated from soil was due to development of phenotypic resistance to predation. It is possible that E. coli ML35 uses a similar mechanism to develop resistance to predation by Bdellovibrio sp.…”
Section: Discussionmentioning
confidence: 98%
“…The predatory phenotypes observed during NC01 co-culture with E. coli ML35 may be the result of a mechanism specific to the prey, the predator, or a combination of the two. Other researchers have observed prey population recovery [66,67], and Shemesh and Jurkevitch demonstrated that recovery of Erwinia carotovora in co-cultures with Bdellovibrio isolated from soil was due to development of phenotypic resistance to predation. It is possible that E. coli ML35 uses a similar mechanism to develop resistance to predation by Bdellovibrio sp.…”
Section: Discussionmentioning
confidence: 98%
“…This is relevant considering that in vivo environments are more structurally complex than buffer systems. Baker and collaborators showed that there are differences between predation in buffer and serum, highlighting both the potential and limitations of B. bacteriovorus HD100 acting therapeutically against K. pneumoniae in serum, stimulating future research into the medicinal behaviors and dosing of this living antibacterial [93]. A comprehensive mathematical framework should consider interactions with the immune system, environmental conditions, and interactions with commensals in order to provide guidance for in vivo application and help researchers to design further dose schedules and therapeutic tests of predators.…”
Section: Mathematical Model Of Predationmentioning
confidence: 99%
“…Elimination of flagella biosynthesis did not impact predation, as well, suggesting that flagellin does not serve as a predator-binding site. Although the motility of the prey might alter predator-prey encounter, the prey to predator ratio, as well as the small liquid volume used in the study is likely to allow sufficient random collisions of predator and prey, regardless of prey motility 26 , 27 . Koval and Hynes suggested that the paracrystalline protein surface layer (S-layer) of Aquaspirillum serpens, A. sinuosum and Aeromonas salmonicida provides protection from B. bacteriovorus predation 28 .…”
Section: Discussionmentioning
confidence: 99%